The impact of lymphadenectomy on survival endpoints in women with early stage uterine endometrioid carcinoma: A matched analysis. (March 2017) - Ghanem, Ahmed I; Khan, Nadia T.; Mahan, Meredith; Ibrahim, Ahmed; Buekers, Thomas; Elshaikh, Mohamed A.
Abstract: Objectives: The role of pelvic lymphadenectomy (LA) in women with stage I endometrial carcinoma (EC) is controversial. The objective of this study is to investigate the prognostic impact of LA on survival endpoints in matched cohorts of women with stage I EC solely of endometrioid histology. Survival endpoints included recurrence-free (RFS), disease-specific (DSS) and overall survival (OS). Methods and materials: Patients with FIGO stage I EC who underwent hysterectomy with LA as part of their surgical staging between 1/1990 and 6/2015 were matched to a similar group that underwent hysterectomy without lymphadenectomy (NLA), based on stage, grade and adjuvant management. Univariate and multivariate modeling with Cox regression analysis was carried out for predictors of survival endpoints. Results: 870 women constituted the study cohort (435 in each group). Median number of dissected lymph node in the LA group was 9 (range, 5–75). There was no statistically significant difference between the two groups in regards to 5-year OS (87.2% for LA vs. 91.7% for NLA) ( p  = 0.36), DSS 97.7% vs. 98% ( p  = 0.54) and RFS (93.7% vs. 90% ( p  = 0.08), respectively. Lymphadenectomy was not a predictor of any of the studied survival endpoints. On multivariate analysis for the entire cohort, older age, deep myometrial invasion and higher tumor grade were predictors of worse RFS. For DSS, higher tumor grade, lower uterine segment (LUS) involvement and FIGO stage IB were significant predictors of worse outcome. For OS, older age and LUS involvement were the only two independent predictors for shorter OS. Conclusions: After matching for FIGO stage, grade and adjuvant management, it appears that lymphadenectomy in women with stage I EC does not impact survival endpoints.